Pengaruh Good Corporate Governance Dan Profitabilitas Terhadap Harga Saham - Robby Swarly; Daryanto Hesti Wibowo (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
This study has the objective to determine how much influence corporate governance and profitability on the price of shares listed on the Stock Exchange in 2017-2019. Population taken as an object of observation amounted to 28 companies manufacturing sub-sectors of the food and beverage industry. Determination of the sample using purposive sampling method and obtained 45 data sampled based on certain criteria. Data analysis technique used in this research is descriptive statistics, test classic assumptions, hypothesis testing. The results of this study indicate that good corporate governance has no significant effect on stock prices and has an effect of .658 or 65.8%. Return on assets has a significant effect on stock prices and has an effect of .728 or 72.8% on stock prices. Based on the results of the F test that good corporate governance and profitability have an effect simultaneously (simultaneously) and have an influence value of .616 or 61.6%.